Studi Resepsi Khalayak terhadap Disinformasi Pandemi Covid-19 pada Media Sosial di Yogyakarta - Wirasti, Murti Kusuma; Wahyono, Sugeng Bayu (Jurnal Komunikasi, 2024)
This study aims to understand and analyze public reception of disinformation in Yogyakarta using Stuart Hall's encoding-decoding theory. The study used a qualitative method. Data were collected through in-depth interviews with two types of informants, namely santri and abangan. This study found that audience reception of COVID-19 pandemic disinformation varied, some were in a dominant hegemonic, negotiating, or oppositional position. The findings of this study confirm the thesis of reception studies which state that every message spread in the media is received polysemically. However, in contrast to the assumptions of reception studies, the position of audience reception at each reading position which is fixed and comes from the same audience is not true. On the contrary, this study found that audience acceptance can change, sometimes in a dominant hegemonic code, sometimes in a negotiating position, and even an oppositional code. Changes in acceptance positions are highly dependent on the issues contained in the COVID-19 pandemic disinformation message.